Analysis of impact of leikonat hardener and microwave energy on the adhesive joint strength - Медвідь, Олеся Григорівна; Олійникова, Валентина Василівна; Свістунова, Людмила Тимофіївна (Eastern-European Journal of Enterprise Technologies, 2014)
A new polychloroprene adhesive composition with increased adhesion strength for gluing bottom parts of footwear was theoretically developed and practically created. The dependence of its holding strength on the content of fillers: modified kaolin, diphenyl guanidine, carbon black DG-100 and leikonat hardener and its benefits in terms of physicomechanical and chemical indicators was proved. As a result of the research, an increase in the adhesion strength of polychloroprene adhesives for footwear manufacture was achieved. The main components of the polychloroprene adhesive composition are nairit NT, gasoline BR1 or BR2, ethyl acetate of the grade A, modified kaolin, diphenyl guanidine, carbon black DG-100 and leikonat. Adding 5% leikonat and microwave energy irradiation increases adhesion strength by 59%. Modified adhesive composition can be recommended for the manufacture of special footwear. The technological standards and modes of assembly of uppers and footwear using microwave energy and modified adhesives in the footwear industry to improve the physicomechanical properties of ready shoes were determined.